Formulation, Evaluation And Study Of Effect Of Hydrophilic Polymers On Release Rate Of Cefixime Floating Tablets - YASH PAUL,; MANOJ KUMAR,; BHUPINDER SINGH, (International Journal of Pharma and Bio Sciences, 2011)
Floating matrix tablets of cefixime trihydrate were developed to prolong gastric residence time and to increase drug absorption and hence bioavailability. Hydrophilic polymers viz. HPMC K4M and Xanthan gum were incorporated in varied proportions to develop floating matrix tablets of cefixime by direct compression method. Buoyancy was achieved by adding an effervescent mixture of sodium bicarbonate and anhydrous citric acid. In vitro drug release studies were performed, and the drug release data were fitted into zero order, first order, Higuchi,s model and Korsmeyer-peppas kinetic models. The optimized formulation composed of 15% w/w of HPMC K4M exhibited maximum drug release (94.71±0.20%) in 12 h, buoyancy lag time was < 1 min, and the tablets remained buoyant for >12 h. All the formulations exhibited hardness, friability, weight variation and drug content values well within the prescribed limits, indicating that the prepared tablets were of standard quality. FTIR studies of the pure drug, its physical mixture with polymer blend showed that no polymorphic changes occurred during manufacturing of tablets. Optimized tablet formulation exhibited no significant change in physical appearance, drug content, total buoyancy time, or in vitro dissolution pattern after storage at 40°C/75% relative humidity for 3 months.